Diuretic effect of Caesalpinia bonduc in rats - Ajay Khedkar; Yuvaraj D. Mandavkar; Gulab Shinde; Pallavi Khalure; Pravin Dere (Bangladesh Pharmacological Society, 2011)
The diuretic effect of aqueous and methanol extracts of the dried seeds of Caesalpinia bonduc was studied in normal rats. Extracts were administered orally at two doses and furosamide was used as standard drug. Urine volume was significantly increased by the two doses of aqueous and methanol extracts in comparison to control group. While the excretion of sodium was also increased by both extracts, potassium excretions were only increased by the aqueous and methanol extracts at a higher dose. The present study provides a quantitative basis for explaining the use of seeds extracts of C. bonduc as a diuretic agent.